Social, economic and environmental impacts of food loss and food waste - Carretero García, Ana (Przegląd Prawa Rolnego, 2018)
The aim of the article is to present the social, economic and environmental conditions underlying food loss and waste. According to the United Nations Food and Agriculture Research Authority, every year 1.3 billion tonnes of food are wasted worldwide, while around 1 billion people suffer from malnutrition. In order to counteract these negative tendencies, the European Commission has developed a new European internet platform dedicated to counteracting food loss and food waste. The platform is intended to support all those who wish to engage in the efforts to eliminate food waste at all stages of production, to promote best market practices in agricultural activity and production, to monitor progress in combating food loss and food waste, and to encourage cross-sectoral cooperation. According to the author, although the measures taken by the European Union in this areadeserve to be welcomed, they are nevertheless inadequate. Food waste is a consequence of many factors that affect the final and actual value of a product. These include, in particular, the social and environmental costs generated by the production and transport of food, as well as costs associated with the process of preparing food for consumption. In order to counteract this situation, measures should be taken to introduce substantive changes in the way food is produced, processed, distributed and consumed, which would contribute to the creation of a more environmentally sustainable and socially responsible production process.